Search of microbiological and immunological signatures of white plague disease in reef-building corals in the Colombian Caribbean. (2014)
Coral reefs posses an immense biodiversity comparable only to that of the tropical rain forest. In Colombia coral reefs occupy an area of 2.860 km2, with 99% located in the Caribbean, and they play a key role in the economy and social structure of costal communities. However, coral reefs are disappearing at an alarming pace that range from 5.5-9.2% a year in the Caribbean. Infectious diseases are thought to be the leading cause of such dramatic decline and current evidence suggests that their emergence is associated with deterioration of local and global environmental conditions. The most prevalent coral disease in the Caribbean is the White Plague Disease (WPD), affecting at least 53 species. Identification of etiological agents, however, has been problematic. This is due in part to the fact that only ~2% of bacteria can be cultured and that most coral diseases are likely to be caused by consortia of different bacteria. In addition, little is known about the factors that determine coral susceptibility or resistance to diseases. In retrospect, most efforts have failed to consider the dynamic interaction between microbial communities, the coral immune competence, and the environment. Corals are symbiotically associated to microbial communities that might change their relative densities, range, and virulence properties in response to variations in the environment or host immunity. In turn, immunity can be affected by variations in microbial communities and environmental factors. Thus, a complex network of interactions between microorganisms, the coral immune system, and the environment defines the health - disease balance. We aim to characterize the bacterial diversity associated to Montastraea sp. corals from Santa Marta Bay (Colombia) affected by WPD, as a signature of the disease and, in addition, to identify immune-related proteins differentially expressed between healthy and diseased corals as a proxy for their immune competence. The type and relative densities of bacterial communities consistently present in diseased corals will give insights into the WPD pathogenesis and will serve as a biomarker for disease progression and pathogenesis. Likewise, the characterization of the coral immune proteome will set the basis to understand the defense mechanisms of corals against diseases. The research team involved in this proposal is conformed by specialists in microbiology, genomics, proteomics, molecular biology, and comparative immunology, reflecting the interdisciplinary character of the proposal. This proposal reflects a strong integration of education with state-of-the-art research, through the formation of pre- and postgraduate students and design of new curricula. Finally, at least two publications in international journals will derived from this project, and the results will be presented in international and national scientific meetings.